Elasto-Plastic Normal Contact of Three-Dimensional Fractal Surfaces Using Halfspace Theory - Willner, Kai (Journal of Tribology, 2004)
The elasto-plastic normal contact of fractal surfaces is investigated. To study the influence of several surface parameters like fractal dimension and resolution, the surfaces are numerically generated using a special form of the structure function which is motivated by measurements of real rough surfaces. The contact simulation uses an iterative elastic halfspace solution based on a variational principle. A simple modification allows also the approximative solution of elasto-plastic contact problems. The influence of different surface parameters is studied with respect to the load-area relationship and the load-gap relationship. The simulations show that for realistic surface parameters the deformation is always in the plastic range. © 2004 by ASME.
UnivIS-Import:2015-03-09:Pub.2004.tech.FT.FT-TM.elstop